Simulation of Few Bifurcation Phase Diagrams of Belousov-Zhabotinsky Reaction with Eleven Variable Chaotic Model in CSTR. Issue 2 (2009) - Swathi, B.; Kulkarni, V. R.
Abstract : Simulation of the Gyorgyi, Rempe and Field eleven variable chaotic model in CSTR [Continuously Stirred Tank Reactor] is performed with respect to the concentrations of malonic acid and [Ce(III)]. These simulation studies show steady state, periodic and non-periodic regions. These studies have been presented as two variable bifurcation phase diagrams. We also have observed the bursting phenomenon under different set of constraints. We have given much importance on computer simulation work but not included the experimental methods in this paper.